Improving the effectiveness of the South African anti-corruption agencies and strategies: lessons from Botswana, Hong Kong and Singapore - Lekubu, Bernard Khotso (Acta criminologica, 2019)
No matter how well-crafted and well-intentioned anti-corruption normative frameworks are formulated, they all come down to nothing if, and when, anti-corruption institutions are tasked with implementing anti-corruption frameworks that are ineffective, or do not produce the expected positive results. This article draws some significant and comparative lessons from Hong Kong, Singapore and Botswana, focussing on their anti-corruption agencies, and their respective effectiveness in combatting corruption. Another important factor informing the choice of these countries is their Transparency International rankings. It is further acknowledged in this article that these types of anti-corruption agencies may differ according to the ambit of their functions. The independent anti-corruption agencies in Hong Kong, Singapore and Botswana have proved to be relatively successful and can provide valuable lessons for South African. Hong Kong, Singapore and Botswana have some common and interpretable patterns in combatting corruption. Importantly, their anti-corruption agencies owe their successes to political support, better resources, organisational autonomy and independence. These attributes, unfortunately, are lacking in the current South African anti-corruption machinery. What anti-corruption approach and model should South Africa adopt? This article argues for a single-agency model or a model that fuses the strong characteristics of a multi-agency with a single agency. Part 2 of this article deals with the anti-corruption frameworks of the selected countries used for comparative purposes. Part 3 and Part 4 deal with the lessons learnt from the three selected country jurisdictions.